Organ‐specific immune response in lethal SARS‐CoV‐2 infection by deep spatial phenotyping. Issue 5 (15th May 2022) - Balachander, Akhila; Lee, Bernett; Biswas, Subhra K; Lye, David C; Lin, Raymond TP; Leo, Yee‐Sin; Chui, Paul; Ng, Lisa FP; Renia, Laurent
Abstract: Objectives: Immunopathology of ongoing COVID‐19 global pandemic is not limited solely to pulmonary tissue, but is often associated with multi‐organ complications, mechanisms of which are intensely being investigated. In this regard, the interplay between immune, stromal cells and cytokines in pulmonary and extrapulmonary infected tissues, especially in young adults (median age 46 years, range 30–53 years) without comorbidities, remains poorly characterised. Methods: We profiled lung, heart and intestinal autopsy samples from five SARS‐CoV‐2‐infected cases for 18–20 targets to detect immune, cytokine and stromal cell status at subcellular resolution by a novel IHC‐based deep‐phenotyping technique, iSPOT (immunoSpatial histoPhenOmics using TSA‐IHC), to assess spatial and functional patterns of immune response in situ, in lethal COVID‐19 infection. Results: SARS‐CoV‐2‐infected autopsy samples exhibit skewed counts of immune populations in all samples with organ‐specific dysfunctions. Lung and ileal tissue reveal altered architecture with marked loss of tissue integrity, while lung and heart tissue show severe hyperinflammation marked by elevated TNF‐α in heart tissue and additionally IL‐6, IFN‐γ and IL‐10 cytokines in lung samples. Conclusion: With resurgence of infection in younger populations, single‐cell cytokine localisation in immune and stromal structures provides important mechanistic insights into organ‐specific immunopathology of naïve SARS‐CoV‐2 infection in the absence of other comorbidities. Abstract : This study characterises the immunopathology of SARS‐CoV‐2 infection in pulmonary and extrapulmonary tissues using a novel and sensitive deep in situ spatial proteomic multiplexing technique, iSPOT. With resurgence of infection in younger populations, single‐cell cytokine localisation in immune and stromal compartments provides important mechanistic insights into organ‐specific immunopathology in lethal COVID‐19 infection.